The Effect Of Service Quality And Academic Information Systems Quality On Student’s Satisfaction - Astri Ayu Purwati; Muhammad Luthfi Hamzah; Nyoto Nyoto; Amirudin M. Amin (International Journal of Economics Development Research (IJEDR), 2022)
The research was conducted on Riau University Pekanbaru. This aims of study to determine the effect of service quality dimensions as seen from 5 dimensions of responsiveness, reliabilty, empathy, assurance, and tangible, then this study aims to determine the effect of quality of academic information systems dimensions as seen from 2 dimensions of system quality and quality of information towords college student satisfaction is following Riau University Pekanbaru. In this study, data were collected by using questonnaire to 400 respondents, which aims is used, include validity test, reliability test, classic assumptions test (normality, heteroscedasticity and multicolinearity), multiple linear regression analysis, goodness of fitest (F test, t test, the coefficient of determination). Data obtained then processed using SPSS program version 19.0, where the value of determination coefficient obtained by 40,6% which means that independent variables is responsiveness, reliability, empathy, assurance, tangible, system quality and quality of information have an effect of the dependent the remaining 59,4% is influenced by other variables not observed in this research. Keywords : Responsiveness, reliability, empathy, assurance, tangible, system quality and quality of information.